Plastic money : constructing markets for credit cards in eight postcommunist countries - Rona-Tas, Akos; Guseva, Alya, 1974- (Stanford University Press, 2014)
In the United States, we now take our ability to pay with plastic for granted. In other parts of the world, however, the establishment of a ""credit-card economy"" has not been easy. In countries without a history of economic stability, how can banks decide who should be given a credit card? How do markets convince people to use cards, make their transactions visible to authorities, assume the potential risk of fraud, and pay to use their own money? Why should merchants agree to pay extra if customers use cards instead of cash? In Plastic Money, Akos Rona-Tas and Alya Guseva tell the story of ...